1998
DOI: 10.1046/j.1432-1327.1998.2530778.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the non‐specific cross‐reacting antigen gene, a member of the carcinoembryonic antigen gene family up‐regulated in colorectal carcinomas

Abstract: Human non-specific cross-reacting antigen (NCA), a close relative of the tumor marker human carcinoembryonic antigen (CEA), is also an in vitro homotypic intercellular adhesion molecule capable of inhibiting differentiation when expressed ectopically by myoblasts. Moreover, NCA appears to be overexpressed at the transcriptional level to a greater extent and more frequently in colorectal carcinomas than CEA. This study examines the transcriptional control mechanisms responsible for orchestrating NCA expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…TATNCCAAT‐less genes can generally be grouped into: (i) constitutively active house‐keeping genes with relatively G/C‐rich promoter regions, SPI sites and often multiple transcriptional start sites; or (ii) genes lacking G/C‐rich regions that have tightly clustered transcriptional start sites that are differentially or developmental regulated . However, in contrast to other TATNCCAAT‐less genes, CEACAM family genes possess features from both groups . They have G/C‐rich promoter regions and SPI sites, but they also have clusters of transcriptional start sites and are differentially expressed.…”
Section: Carcinoembryonic Antigen/carcinoembryonic Antigen‐related Cementioning
confidence: 99%
See 2 more Smart Citations
“…TATNCCAAT‐less genes can generally be grouped into: (i) constitutively active house‐keeping genes with relatively G/C‐rich promoter regions, SPI sites and often multiple transcriptional start sites; or (ii) genes lacking G/C‐rich regions that have tightly clustered transcriptional start sites that are differentially or developmental regulated . However, in contrast to other TATNCCAAT‐less genes, CEACAM family genes possess features from both groups . They have G/C‐rich promoter regions and SPI sites, but they also have clusters of transcriptional start sites and are differentially expressed.…”
Section: Carcinoembryonic Antigen/carcinoembryonic Antigen‐related Cementioning
confidence: 99%
“…Studies on transcriptional regulation of the CEACAM family genes have previously been performed with human CEACAMl and CEA-CAM6 genes. 23 Research on the regulation of other CEACAM family genes in humans and other species is still scarce. The upstream promoter sequences of CEACAM1 and CEACAM6 genes lack the classical TATA and CCAAT boxes.…”
Section: Transcriptional Regulation Of Carcinoembryonic Antigen/carmentioning
confidence: 99%
See 1 more Smart Citation
“…In many tissues, more than one CEACAM family member are expressed concurrently. For example, CEACAMs 1, 5, and 6 are often expressed in ovarian, endometrial, cervical, breast, lung, and colon carcinomas, and may be useful as biomarkers in cancer [43][44][45][46][47]. A CEACAM5 expressing measles virus has entered phase I trials in ovarian cancer [48].…”
Section: Introductionmentioning
confidence: 99%
“…The region within 284 bp upstream of the translational start site of the NCA gene was found to be capable of directing high levels of expression in functional promoter assays. The study revealed the role of upstream stimulating factors USF1 and USF2 in the activation of CEACAM6 as well as by the stimulatory proteins Sp1, Sp3 and Sp5 34 35. Another study revealed that expression of recombinant thyroid transcription factor-1 (TTF-1) increased CEACAM6 in a dose-dependent fashion in lung tissue, showing the role of this factor in CEACAM6 gene expression 36.…”
Section: Discussionmentioning
confidence: 92%